Prediksi Sisa Umur Generator Dengan Metode Pengujian Dielektrik Pada Stator Generator Unit 2 PLTU Ombilin - Alex Fernandes; Samsurizal Samsurizal (KILAT, 2023)
Electrical demand getting higher every year, therefore reliability is needed in distributing electrical energy to consumers, to realize this reliability, electrical equipment that can work properly is needed so that there are no obstacles in the operating system, one of the electrical equipment that has a very important role very important in a steam power plant is the generator, along with the age of use of the generator which has been more than 20 years at the Ombilin PLTU, there must be some obstacles including its isolation which can cause current leakage and total damage to the generator. The purpose of the dielectric test. This research was conducted to predict the remaining life of the generator due to dielectric problems that occur in the insulation system by conducting dielectric tests and finding solutions to extend the life of the generator. The method used in this study using the D-MAP method with the formula used from the values obtained in dielectric testing, such as tan delta testing, leakage current testing, and partial discharge testing. The results of this dielectric test get a breakdown voltage of 42.48% and get a prediction of the remaining life of the generator for another 4 years. And to improve the breakdown voltage value, a revarnish is carried out to improve the partial discharge value.